2013
DOI: 10.1002/esp.3473
|View full text |Cite
|
Sign up to set email alerts
|

The geomorphological context and impact of the linear emergent macrophyte, Sparganium erectum L.: a statistical analysis of observations from British rivers

Abstract: This paper explores the geomorphological context and impact of the widely‐occurring, linear emergent macrophyte, Sparganium erectum. Forty‐seven sites across Britain were selected for field investigation, spanning the range of environmental conditions within which Sparganium erectum had been found to be present in previous analyses of national data sets. A combination of descriptive graphs and statistics, principal components analysis, and Kruskal–Wallis tests were used to explore the large multivariate data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Second, the analysis of UK data sets at site to national scales showed that emergent aquatic plants can also interact with hydrogeomorphological processes to drive a cycle of pioneer landform development and floodplain construction (e.g. Gurnell et al ., ). Third, a new conceptual synthetic model of ‘changing river channels’ (Gurnell et al ., ) was proposed for gravel‐bed rivers in humid temperate environments, which (a) incorporates both riparian and aquatic vegetation, (b) identifies that particular plant species can act as physical ecosystem engineers ( sensu Jones et al ., , ) driving pioneer landform development and cycles of river margin evolution, and facilitating colonization by other plant species and (c) proposes that the character and dynamics of the pioneer landforms and their associated river margins vary with river type (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the analysis of UK data sets at site to national scales showed that emergent aquatic plants can also interact with hydrogeomorphological processes to drive a cycle of pioneer landform development and floodplain construction (e.g. Gurnell et al ., ). Third, a new conceptual synthetic model of ‘changing river channels’ (Gurnell et al ., ) was proposed for gravel‐bed rivers in humid temperate environments, which (a) incorporates both riparian and aquatic vegetation, (b) identifies that particular plant species can act as physical ecosystem engineers ( sensu Jones et al ., , ) driving pioneer landform development and cycles of river margin evolution, and facilitating colonization by other plant species and (c) proposes that the character and dynamics of the pioneer landforms and their associated river margins vary with river type (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They are also well below the 60 to 110 W.m −2 identified by Gurnell et al . () for channels that support a maximum 25% to 5% cover of the common emergent macrophyte Sparganium erectum .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, removal of channel reinforcement leads to a greater availability of sites for colonization by aquatic plants. This combination of changed environmental conditions that often accompanies restoration of urban rivers, not only supports an increase in fine sediment supply and aquatic plant cover but also the trapping and reinforcement of fine sediments by the plants, particularly by emergent macrophytes, to build submerged and eventually emergent river landforms, which can induce channel widening and migration (Gurnell et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Both submerged (Cotton et al ., ) and emergent (Gurnell et al ., ) macrophytes have been shown to retain fine sediment and to build landforms on the river bed and margins. Emergent plants, in particular, have been shown to retain and reinforce sediments (Liffen et al ., ) to the extent that these plants can act as ecosystem engineers, initiating island and bench development and inducing channel migration in low‐energy river environments where channel dynamics would otherwise be limited (Gurnell et al ., ). In non‐urban situations, plant‐engineered landforms have also been shown to retain nutrients and seeds, providing a seed bank to support vegetation succession as the retained sediments aggrade above the low‐flow water level (O'Hare et al ., ), and concentrating flows between vegetated patches, leading to exposure of the underlying river bed sediments (Gurnell, ).…”
Section: Introductionmentioning
confidence: 99%